Preventing childhood obesity in early care and education programs (American Academy of Pediatrics, 2020)
"This coveted resource provides the latest national standards describing evidence-based best practices in nutrition, physical activity, and screen time for early care and education programs. The standards are for all types of early care and education settings--centers and family child care homes."--Provided by publisher